Novel banana-discotic hybrid architectures - Bisoyi, Hari Krishna; Srinivasa, H. T.; Kumar, Sandeep (Beilstein Journal of Organic Chemistry, 2009)
Here we present the design and synthesis of novel banana-discotic dimers and banana-bridged discotic dimers. The chemical structures have been characterized by spectral techniques and elemental analysis. The thermal behaviors of the compounds have been investigated by polarizing optical microscopy and differential scanning calorimetry. None of these synthesized compounds exhibit any liquid crystalline property probably because of the incompatibility of the bent-core with the discotic core.
Keywords: bent-core; dimer; discotic; triphenylene